Comportamento da variabilidade da frequência cardíaca em pacientes submetidos ao tilt-test - Silva, Arnaldo Pedro da (2018)
The Autonomic Nervous System (ANS) plays an important role in regulating the physiological processes of the human organism both in normal and pathological conditions. It also accounts for the automatic control of the body when facing environmental changes. In this way, it can be observed that the organism has a mechanism that allows body adjustments all the times, thus providing its stability (homeostasis). It is a complex system that, even today, needs to be more investigated a better understanding. OBJECTIVES: The purpose of this study is to understand the functioning of the ANS by assessing the behavior of the Heart Rate Variability (HRV) in patients submitted to the Tilt-test. To investigate correlation between the signs and / or symptoms that occurred during the Tilt-test and changes in HRV and to evaluate if there is clinical validity of HRV through the Receiver Operator Characteristics Curve (ROC). MATERIAL AND METHOD: This study comprised 67 patients, who had the Polar RS 8OO CX device attached to their body, with a transmitting belt, connected to the chest of each patient and a watch, fixed to the left wrist. This device made the initial capture of the cardiac signal and has accounted for the measurements of HRV of the patient throughout the exam. Data were transferred to a microcomputer containing the Polar Precision Performance software and the records with at least 95% of the normal sinus RR intervals captured during the initial 20 minutes with the patient in the supine position during the Tilt-test were transformed into time series of fixed length and analyzed with the aid of specific software. Of these patients, 47 presented good quality tachographs for analysis and , afterwards, were divided into two groups: one (+), or symptomatic Group for syncope, during the Tilt-test, with 7 members and another Group (-), considered asymptomatic or negative for syncope, also during the Tilt-test, with 40 individuals. Due to a statistical difference observed between the ages of these two groups, and to meet our goals, an age pairing was performed, where the Group of seven positive individuals was maintained, and 14 (selected) individuals remained in the Group (-). RESULTS: According to the final statistical evaluation, the seven member group was composed of younger and thinner individuals (Age = 22.78±7.01; BMI = 22.60±5.18) and the Group (-) with 14 members (Age = 28.82±10.09; BMI = 25.34±2.82), older and overweight individuals. Regarding the HRV rates, we obtained the following mean values in relation to the (+) Group: rMSSD(ms) = 45.15±16.43; pNN50(%) = 23.38±15.39; LFpow_FFT(n.u.) = 58.51±15.83; HFpow_FFT(n.u.) = 41.34±15.76; LH_HF_ratio_FFT = 2.28±2.53; DFA1 = 0.99±0.15. In relation to the Group(-), they were: rMSSD(ms) = 36,80±21,13; pNN50(%) = 16.40±18.50; LFpow_FFT(n.u.) = 68.20±15.10; HFpow_FFT(n.u.) = 31.67±14.99; LH_HF_ratio_FFT = 3.48±4.07; DFA1 = 1.18±0.19. CONCLUSION: Although some promising mathematical results were found, we concluded that HRV analysis by linear methods in patients submitted to Tilt-test did not demonstrate sufficient statistical significance as a device to predictic symptomatic or positive patients for syncope , submitted to the Tilt-test in the initial 20 minutes of the supine examination, compared to asymptomatic or negative patients for syncope: (rMSSD(ms)(+) and rMSDM(ms)(-) p = 0.3726; pNN50(%)(+) and pNN50(%)(-)p = 0,4019; LFpow_FFT(n.u.)(+) and LFpow_FFT (n.u.)(-) p = 0.1987; HFpow_FFT(n.u.)(+) and HFpow_FFT(n.u.)(-) p = 0.1788; LH_HF_ratio_FFT(+) and LH_HF_ratio_FFT(-) p = 0.4917). In this study, the non-linear index DFA1 (DFA1(+) and DFA1(-) p = 0.0343) was the only HRV variable that presented statistical significance in the comparation. This isolated variable still needs to be better understood as well as studied and more used in research for better comprehension of the SNA dynamics.